2011
DOI: 10.1590/s0102-79722011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a short-form version of the Brazilian state-trait anxiety inventory

Abstract: The Brazilian State-Trait Anxiety Inventory has been widely used to measure state (STAI-S) and trait (STAI-T) components of anxiety. The present work developed and evaluated a short version of the STAI-S and STAI-T in a large sample of Brazilian subjects. The first study selected short-form scales. The second one employed factor analyses to investigate whether each of the two short-form scales presented a well-defined and balanced structure with both anxiety-present and anxiety-absent factors. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 16 publications
0
63
0
16
Order By: Relevance
“…8,[13][14][15][16] For the statistical analysis, the data were gathered into contingency and frequency tables. The distribution was judged by means of the Kolmogorov-Smirnov test and central trend measurements were expressed as means and standard deviations in normal samples and as medians and interquartile ranges (IQR) in non-Gaussian samples.…”
Section: Methodsmentioning
confidence: 99%
“…8,[13][14][15][16] For the statistical analysis, the data were gathered into contingency and frequency tables. The distribution was judged by means of the Kolmogorov-Smirnov test and central trend measurements were expressed as means and standard deviations in normal samples and as medians and interquartile ranges (IQR) in non-Gaussian samples.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis of the subjects' level of anxiety the short version of the Brazilian State-Trait Anxiety Inventory (STAI) 36 was used. This instrument evaluates both anxiety in terms of state (how the subject feels at that moment) and in terms of trait (how the subject feels usually).…”
Section: Instrumentsmentioning
confidence: 99%
“…STAI has twelve 4-point Likert-scale items (absolutely not = 1; a little = 2; some = 3; and very much = 4) divided into two subscales: a) State anxiety (STAI-S), which regards how the interviewee feels at that moment; and b) Trait anxiety (STAI-T), which regards how the interviewee generally feels. The STAI validation study 18 found internal consistencies of 0.90 and 0.89 for STAI-S and STAI-T, respectively. Cronbach's alphas for the present sample were 0.85 for STAI-S and 0.87 for STAI-T, indicating good internal consistency.…”
Section: Instrumentsmentioning
confidence: 99%
“…The short version of the Brazilian StateTrait Anxiety Inventory (STAI) validated for the Brazilian population by Fioravanti-Bastos et al 18 assessed anxiety. STAI has twelve 4-point Likert-scale items (absolutely not = 1; a little = 2; some = 3; and very much = 4) divided into two subscales: a) State anxiety (STAI-S), which regards how the interviewee feels at that moment; and b) Trait anxiety (STAI-T), which regards how the interviewee generally feels.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation